Respostas
respondido por:
1
a) (-4/3)^0 = 1
**********************
b): (-2/3)^4
4
(- 2) = 2⁴
----- -----
( 3) 3⁴
= 16
-------
81
*********************************
c): (-1/4)^-1
1
( - 4) = - 4
**************************
e): -(-1/3)^-6
6
- ( - 3) = - (729) = - 729
**********************
b): (-2/3)^4
4
(- 2) = 2⁴
----- -----
( 3) 3⁴
= 16
-------
81
*********************************
c): (-1/4)^-1
1
( - 4) = - 4
**************************
e): -(-1/3)^-6
6
- ( - 3) = - (729) = - 729
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás